Fast metabolism food rx ebook 7 powerful prescriptions to feed your body back to health. - Pomroy, Haylie (2016)
“ Fast Metabolism Food Rx gives you real practical programs to nurture the body back to health.”—DEEPAK CHOPRA   From the #1 New York Times bestselling author of The Fast Metabolism Diet comes “a complete guidebook that will help you regain your health and reverse chronic disease with your own kitchen pharmacy” (Alan Christianson, NMD, New York Times bestselling author of The Adrenal Reset Diet ).    Want to feel great, disease-proof your body, and live at your ideal weight? Then eat your medicine! Celebrated nutritionist Haylie Pomroy has just the prescription for you, offering solutions for the seven most common ways your metabolism misfires and leads to exhaustion, excess weight, and illness.    After multiple health challenges threatened Haylie’s life, she set out on an investigative journey that was life-changing—and lifesaving. She shares her personal story for the first time in Fast Metabolism Food Rx and presents the powerful food programs she created based on the methods and philosophies that saved her life and helped her thrive. For decades, these food therapies have provided profound clinical results for thousands of patients. Our bodies are always talking and communicating their needs; we just need to learn how to listen. Maybe our energy is off, we don’t feel right, we have indigestion, or our body shape is morphing in ways we don’t recognize or like. Or our biochemistry is changing, raising our cholesterol, making us irritable, reactive, or “foggy.” These—and other, more serious medical issues, like pre-diabetes and immune complications—hide a specific problem, for which food, not drugs, is the answer.   So, if you’re suffering from GI issues, fatigue, out-of-whack-hormones, mood and cognition difficulties, elevated cholesterol, blood sugar control problems, or an autoimmune problem, Fast Metabolism Food Rx has the solution for you. With targeted eating plans, you can feed your body back to a vibrant, energetic, and thriving state.